A survey on Current Procedural Terminology (CPT) by Iranian Urological Association - Allameh, Farzad; Basiri, Abbas; Abedi, Amir reza; Ghahestani, Seyyed Mohammad; montazeri, saeed; Fakhar, Vahid (Urology Journal, 2020)
Purpose: The purpose of Current Procedural Terminology (CPT) is to offer a universal language to describe medical services. The elaborate systems designed by high-income countries are not fully applicable in ones with limited resources. Therefore, in the current study we aimed to ask urologists' opinion about deploying relative value units in valuation of medical services in Islamic republic of Iran. Materials and Methods: A group of appointed urologists first selected 15 urological surgeries as exemplar urological procedures. Next, urologists around the country were asked to fill out an online questionnaire comparing these procedures with standard one (varicocelectomy). Then, mean scores of four categories (Difficulty, duration, adverse events and legal issues) were determined separately for each of the 15 procedures. Subsequently, mean score for each surgery was measured using the calculated mean scores of the four aforementioned categories. Results: 273 urologists completed an online questionnaire. All of the calculated codes were higher compared to the current codes. Urethroplasty showed the least increment with 25.22 equivalent to 51.69% while extracorporeal shock wave lithotripsy showed the most increment of 63.59 equivalent to 114.37%. Conclusion: Although CPT is an important tool in valuation of medical services, making modifications to it, especially in low-to-middle-income countries seems necessary. In this survey, we aimed to evaluate current surgical codes for urological procedures based on urologists' opinion. All of the calculated codes were higher compared with current codes. This, indicated the necessity of making changes in relative value units of urological procedures.